Bentuk dan Struktur Pertunjukan Tari Reog Ponorogo di Desa Tri Mulya Agung Kecamatan Lalan Kabupaten Musi Banyuasin - Lestari, Desi Dwi; Dhony, Nugroho Notosutanto Arhon; Adoma, Auzy Madona (ANTHOR: Education and Learning Journal, 2022)
The purpose of this study was to describe the form and structure of the Ponorogo Reog dance performance. The method used in this research is a descriptive qualitative method, with data collection techniques using observation, interviews, and documentation. The result of theanalysis of research data on Ponorogo is a dance that grows and develops in the village of Tri Mulya Agung this dance is usually danced by seven people. Reog Ponorogo dance is usually performed at weddings, circumcisions, etc, this dance uses the dadak peacock property made of bamboo and rattan, and artificial horses made of woven bamboo, while the costumes use clothes, udengan, cute, sempyok, katok panji, stagen, sampur, jarik binggel sikel, and boroboro. The accompaniment music used in the Reog Ponorogo dance performance is saron, drums, kenong, kempul, gongs, and angklung. While the structure of the show includes the opening, the core, the closing